Study on Tradeoffs in Detection of Malicious Data Injections in Wireless Sensor Networks. (2016) - Vijayan, Nisha; Johny, Alphonsa
Abstract: Wireless Sensor Networks are widely being used today. Though efficient, fast and easy to use these wireless sensors are highly vulnerable. Once installed, they do not need any further maintenance. Therefore they are less secure. An attacker can study the network behavior and easily attack these sensors. There are many safety measures taken for this. There are software's available to detect malicious sensors. The greatest challenge in the wireless sensor network security is when more number of sensors are infected. It becomes difficult to decide which sensor is malicious and which is genuine. This leads to the study of Wireless Sensor Network Security. This paper shows various security measures taken and some challenges faced by them.